Estimation of Nicotine in Tobacco Extract Using C8 Column in High Performance Liquid Chromatography - Shekhar, Ravi; Kumar, Santosh; Prakash, Pritam (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Nicotine is the most used toxic substance in spite of mass media awareness. Column used in the estimation of nicotine is found to be the inhibiting factor for its estimation. Objective: To develop a method for nicotine estimation on C8 column in HPLC. Methods: The method involved a model Waters 1515 binary HPLC Pump system interfaced with a 2489 Waters UV/VIS detector, a 4.6 X 250 mm, 5μm beads Symmetry C8 column at 37°C, and an isocratic mobile phase containing 60%: 40% v/ v mixture of 10mM sodium acetate (pH 5.5) and methanol at a flow rate of 1.0ml/min at 256 nm. The method was validated for specificity, linearity, precision, accuracy, the Limit of Detection (LOD), the Limit of Quantitation (LOQ) and system suitability. Results: The HPLC Nicotine peak with average retention time of 3.415 minutes was observed on chromatogram with RSD <0.5%; linearity was greater than 0.99 with acceptable precision (within USP limits of <2.0% RSD) and USP tailing less than 2. LOD was found to be 0.200 μg/ml and Limit of Quantitation (LOQ) was found to be 0.609 μg/ml of nicotine. The average yield of the nicotine extracted by acid base extraction method from tobacco was 1.68% (range: 1.34–2.22%). Conclusion: A HPLC method based on C8 column for analysis of Nicotine was developed and validated successfully. International Journal of Human and Health Sciences Vol. 07 No. 02 Apr’23 Page: 166-170